Barriers to renewable energy technologies penetration: Perspective in Iran. (August 2021) - Oryani, Bahareh; Koo, Yoonmo; Rezania, Shahabaldin; Shafiee, Afsaneh
Abstract: The dominance of conventional fuels in Iran and therefore increasing concerns about its side effects (both environmental issues and economical) has required the Government and policymakers to switch to the adoption of renewable technologies. However, facing some obstacles has lowered the adoption rate of these technologies. Therefore, by applying Analytical Hierarchy Process (AHP) method, this paper tends to identify and rank the main barriers to the development of the three alternatives in Iran, named solar PV, wind turbines, and biomass. From the literature review and experts' viewpoints, thirteen barriers have been identified and accordingly have been grouped into five dimensions, called 1. Economic & financial, 2. Social, cultural, & behavioural, 3. Political & regulatory, 4. Technical, and 5. Institutional. The sensitivity analysis has been conducted to check the stability of the priority ranking of the stated alternatives. The results showed that there are fewer limitations to the development of solar PV, followed by wind turbines and biomass. Therefore, to formulate and frame appropriate policies and strategies to foster the adoption of renewable energy technologies, at the first step, the Government and policymakers must pay more attention to overcome the hindrance to the expansion of solar PV.